NEUROLOGICAL AND HEMODYNAMIC PROFILES OF POST CRANIOTOMY PATIENTS BASED ON SURVIVAL STATUS IN THE INTENSIVE CARE UNIT - Rudi Hariyono Hariyono (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Early neurological and hemodynamic assessment is important in the management of post-craniotomy patients in the intensive care unit (ICU). To describe the distribution of age, sex, MAP, and FOUR scores among post-craniotomy patients according to survival status. A descriptive cross-sectional study was conducted in the ICU of RS Islam Sakinah from 15 February to 18 March 2026. Post-craniotomy patients were enrolled using consecutive sampling. Age was summarized as mean ± standard deviation, sex as frequencies and percentages, and MAP and FOUR scores as median and interquartile range (IQR). The overall mean age was 53.48 ± 16.02 years. Non-survivors were slightly older than survivors (56.00 ± 9.14 vs. 52.52 ± 18.00 years). The cohort consisted of 55% males and 45% females, with similar survival proportions between sexes. Survivors had a median MAP of 90 (88–122) mmHg, whereas non-survivors had a median MAP of 130 (102–130) mmHg and greater hemodynamic variability. Survivors had a median FOUR score of 15 (14–16), while non-survivors had a median score of 8 (2–11). Non - survivors demonstrated higher and more variable MAP values and lower, more heterogeneous FOUR scores than survivors. These findings describe distinct hemodynamic and neurological profiles between the two groups and may support clinical assessment in ICU settings. Further longitudinal studies are needed to evaluate the clinical significance of these parameters.